Biomimetics: Insights into the Adhesive Mechanisms of Tree Frogs using Artificial Mimics (Adv. Funct. Mater. 9/2013). (4th March 2013) - Drotlef, Dirk‐Michael; Stepien, Lukas; Kappl, Michael; Barnes, W. Jon P.; Butt, Hans‐Jürgen; del Campo, Aránzazu
<x xml:space="preserve">Abstract</x> The distinct surface design of tree‐frog toe pads inspires new strategies for improving attachment in the presence of fluid layers. Tree‐frog toe pad mimicks consisting of microstructured soft polymeric surfaces with hexagonal pillars separated by narrow channels reveal the role and the potential of surface patterning for wet adhesion. As reported by Aránzazu del Campo and co‐workers on page 1137, the right combination of surface topograhy and surface energy allows enhancing of adhesive and frictional forces by favoring fluid drainage and establishment of direct contact forces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>